A Continuous Path Algorithm and its Implementation to a Micro Computer Controlled Industrial Robot - Szvoboda, Gabor (My University, 1982)
A continuous path algorithm involving real time co-ordinate transformation is suggested and implemented on a micro-computer for the purpose of controlling a five axes industrial robot. This software and the hardware aspects of the implementation are discussed. Good results prove the viability of the method.
Another algorithm based on cubic spline approximation is briefly analyzed. The servo-drive and robot structural dynamic measurements.
Title: A Continuous Path Algorithm and its Implementation to a Micro Computer Controlled Industrial Robot, Author: Gabor Szvoboda, Location: Thode